2007
DOI: 10.1111/j.1467-7652.2007.00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving containment strategies in biopharming

Abstract: SummaryThis review examines the challenges of segregating biopharmed crops expressing pharmaceutical or veterinary agents from mainstream crops, particularly those destined for food or feed use. The strategy of using major food crops as production vehicles for the expression of pharmaceutical or veterinary agents is critically analysed in the light of several recent episodes of contamination of the human food chain by non-approved crop varieties.Commercially viable strategies to limit or avoid biopharming intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 215 publications
(190 reference statements)
1
38
0
Order By: Relevance
“…Upon chloroplast transformation with high copies of target gene stably integrated into the chloroplast genome, transgenic plants can accumulate recombinant proteins as high as 46% of the total leaf proteins (Arlen et al, 2007;De Cosa et al, 2001). Benefiting from the prokaryotic organization of the chloroplast genome (Arlen et al, 2007;Murphy, 2007;Svab et al, 1990), nearly no gene silencing has been observed in chloroplast bioreactor even when the accumulation of transcripts is 169 times higher in chloroplast than that in nuclear (Lee et al, 2003). In addition, the chloroplast genome can be precisely manipulated because of its small size, in which exogenous genes can be site-specifically integrated into the chloroplast genome via homologous recombination using a DNA sequence derived from the chloroplast genome (Daniell et al, 1998;Sidorov et al, 1999).…”
Section: Advantages and Progress Of The Chloroplast Bioreactormentioning
confidence: 99%
“…Upon chloroplast transformation with high copies of target gene stably integrated into the chloroplast genome, transgenic plants can accumulate recombinant proteins as high as 46% of the total leaf proteins (Arlen et al, 2007;De Cosa et al, 2001). Benefiting from the prokaryotic organization of the chloroplast genome (Arlen et al, 2007;Murphy, 2007;Svab et al, 1990), nearly no gene silencing has been observed in chloroplast bioreactor even when the accumulation of transcripts is 169 times higher in chloroplast than that in nuclear (Lee et al, 2003). In addition, the chloroplast genome can be precisely manipulated because of its small size, in which exogenous genes can be site-specifically integrated into the chloroplast genome via homologous recombination using a DNA sequence derived from the chloroplast genome (Daniell et al, 1998;Sidorov et al, 1999).…”
Section: Advantages and Progress Of The Chloroplast Bioreactormentioning
confidence: 99%
“…The cultivation of transplastomic GM cultivars revealed some disadvantages in respect to containment: Although maternal inheritance is widely assumed to be the general rule in most angiosperms, rare pollen-mediated gene transfer has been detected in a number of cases (Murphy, 2007). Rare, but possible, transmission of plastid DNA via pollen (Cummins, 1998;Lu, 2003;Wang et al, 2004), even with very low levels of paternal gene transfer, may be sufficient for the escape and spread of a transgene (Haygood et al, 2004).…”
Section: Plastid Transformationmentioning
confidence: 99%
“…Plastid transformation has been achieved in many important crops, including tobacco, soybean, potato, tomato, cotton, as well in minor species, such as lettuce, petunia and Lesquerella fendleri (Brassicaceae, cultivated for oil production) and in non-crop systems, such as the alga Clamydomonas reinhardtii (Murphy, 2007). The cultivation of transplastomic GM cultivars revealed some disadvantages in respect to containment: Although maternal inheritance is widely assumed to be the general rule in most angiosperms, rare pollen-mediated gene transfer has been detected in a number of cases (Murphy, 2007).…”
Section: Plastid Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of biological, chemical, and physical methods and their combinations to provide a high level of containment for such biopharmed plants. These measures include transplastomics itself (see Section 5.1), alternative production in non-food/non-feed crops or even non-crop plants, and inducible or transient expression systems (reviewed in Murphy 2007).…”
Section: Public Concerns Associated With Transplastomic Plantsmentioning
confidence: 99%